Case reportEpisodes of severe menorrhagia at menarche in a girl with von Willebrand disease - Christoforidis, Athanasios; Economou, Marina; Athanassiou-Metaxa, Miranda (Archives of Medical Science, 2007)
We describe a case of a 14-year-old girl with von Willebrand disease (vWD) and episodes of severe menorrhagia at menarche, necessitating hospitalization and requiring blood transfusions and administration of purified von Willebrand factor. Further episodes of menorrhagia were successfully prevented with the use of oral contraceptives and uterine bleeding at menses was regulated with the combination of nasal desmopressin and tranexamic acid per os.